Asthma in elite athletes – do they have Type 2 or non-Type 2 disease? A new insight on the endotypes among elite athletes - Rasmussen, Søren Malte; Hansen, Erik Sören Halvard; Backer, Vibeke (Frontiers in Allergy, 2022)
Asthma and exercise-induced bronchoconstriction are highly prevalent in elite athletes compared with the general population. Some athletes have classic asthma with allergic sensitization; however, it seems that a proportion of athletes develop asthma as a result of several years of intensive training. It leads us to believe that asthma in athletes consists of at least two distinct endotypes – classic early-onset, Type 2 mediated asthma, and asthma with later onset caused by exercise which might be classified as non-Type 2 asthma. The purpose of this review is to evaluate the current literature on asthma in athletes focusing on inflammation and examine if asthma in athletes could be characterized as either Type 2- or non-Type 2 asthma.